PEDAGOGICAL ERUDITION AS AN IMPORTANT FACTOR IN TRAINING HIGHLY QUALIFIED PERSONNEL (Universal International Scientific Journal, 2026)
This article scientifically analyzes the content of the concept of pedagogical erudition, its role in the modern education system and its importance in the process of training highly qualified personnel. Pedagogical erudition is characterized by a teacher's broad scientific outlook, methodological training, professional competence and ability to carry out innovative pedagogical activities. The article highlights pedagogical erudition as an important factor in improving the quality of education, modernizing the pedagogical process and developing the intellectual potential of students. The theoretical foundations and practical mechanisms of the formation of pedagogical erudition are also analyzed.
Keywords: pedagogical erudition, pedagogical competence, quality of education, pedagogical skills, innovative education, professional development, pedagogical thinking